FEATURES OF ULTRASOUND EXAMINATION OF THE THYROID GLAND IN PATIENTS WITH HYPOTHYROIDISM - D.D. Usmanova; D.N. Kambarova; N. Kodirov (Central Asian Journal of Medicine, 2024)
In the membranes of erythrocytes in patients with hypothyroidism against the background of chronic migraine, a significant violation of pro- and antioxidant homeostasis is revealed. When studying the indicators of antioxidant protection, their decrease was revealed. At the same time, the content of AOS parameters in the blood plasma in patients with CM and hypothyroidism was noted to decrease in indicators as the duration of headache increased for more than 5 years.